2022
DOI: 10.1037/aca0000331
|View full text |Cite
|
Sign up to set email alerts
|

Why people press “like”: A new measure for aesthetic appeal derived from Instagram data.

Abstract: Be it on Facebook, Twitter, or Instagram, “Like” buttons are all over social media generating huge amounts of data. In this project, we develop methods for leveraging Instagram data with the purpose of developing a measure that is useful as a proxy for the aesthetic appeal of photographs. Based on the metadata of 15,073 photographs from the photographic genres of architecture, dance, and landscape gathered from 9 different Instagram accounts of professional photographers, we compute the Image Aesthetic Appeal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Following on this idea of fast decisions (Outcome Check 1), the use of mobile phones creates a situation in which fast and direct aesthetic responses (“swiping” or “giving likes”; cf. Thömmes and Hübner, 2020 ) are frequent and have become inherently part of the medium use. Related to aesthetic quality, evaluations of motif qualities such as “nice” or “hot” often are made so quickly that they are presumably based on some fast-accessible features of early vision, apparently associated with beauty, or their relative variation from image to image.…”
Section: Introductionmentioning
confidence: 99%
“…Following on this idea of fast decisions (Outcome Check 1), the use of mobile phones creates a situation in which fast and direct aesthetic responses (“swiping” or “giving likes”; cf. Thömmes and Hübner, 2020 ) are frequent and have become inherently part of the medium use. Related to aesthetic quality, evaluations of motif qualities such as “nice” or “hot” often are made so quickly that they are presumably based on some fast-accessible features of early vision, apparently associated with beauty, or their relative variation from image to image.…”
Section: Introductionmentioning
confidence: 99%
“…Individual aesthetic appeal preferences may differ for visuals. What one finds aesthetically appealing, others may not see it appealing (Thömmes & Hübner, 2020).…”
Section: Aesthetic Appealmentioning
confidence: 99%
“…As a result, they found that the most shared images are not necessarily aesthetic, despite the fact aesthetic images are more likely to be visually interesting to people. Furthermore, the aesthetical appeal of images has been shown to be a measurement element that predicts the number of likes quite well [47].…”
Section: Aesthetical Appeal: Color and Compositionmentioning
confidence: 99%